Clinical and Electrophysiological Evaluation of Electrical Stimulation in Patients with Bell’s Palsy - Çelik, Fatma; Ayyıldız, Aylin; Çiftci İnceoğlu, Selda and Yılmaz, Figen and Çelik, Mustafa and Kuran, Banu (Acta medica Lituanica, 2024)
Background: The objective of this study is to assess the clinical and electrophysiological effectiveness of electrical stimulation in patients diagnosed Bell’s palsy (BP), and to examine its impact on potential complications that may arise during the course of the illness.Methods: Thirty patients diagnosed with BP were enrolled and randomized into two treatment groups of 15 patients each. The treatment group (TG) received 15 sessions of electrical stimulation (ES), infrared, and exercise therapy, 5 days a week for 3 weeks, while the control group (CG) received sham ES, infrared, and exercise therapy. Evaluations were conducted by electromyography before treatment and at 1 and 3 months after the end of treatment for all patients.Results: When evaluating patients in both groups based on the side where the BP developed, electrophysiological examination showed an increase in the rate of synkinesis in both the TG and CG. However, there was no statistically significant difference between the two groups. The study found that ES did not reduce the presence of synkinesis in denervated muscles. However, the nerve conduction studies of the studied branches of the facial nerve showed a decrease in distal latencies and an increase in amplitudes of compound muscle action potentials, indicating that ES has a positive effect on nerve regeneration.Conclusion: ES resulted in a notable reduction in distal latency values within the treatment group. Additionally, ES was found to significantly alleviate depressive symptoms, although it did not result in an improvement in overall quality of life. Therefore, ES is considered a safe treatment method that can be used in the treatment of BP.